La experiencia cuencana como "rito de paso" de la migración académica española a Ecuador - María del Rocío Pérez-Gañán; María Jara Rodríguez-Fariñas (Revista Iberoamericana de Estudios de Desarrollo)
The socio-economic crisis Spain has experienced since 2008, connected with the process of the Ecuadorian government to attract qualified human resources abroad, both converged in a massive insertion of Spaniards in as researchers and professors at universities in Ecuador during the period 2011-2015. Within the framework of a global knowledge economy that generates asymmetric processes of concentration, expulsion and instrumentalization of human potential, this study attempts to understand, through a biographical method (analysis of the seven stories of migration of Spanish academics), the mechanisms activated in the dynamics of North-South academic mobility, in these processes of qualified labor migration, expelled in a search for professional advancement, to later access an academic career in the country of origin.